The use of AI in formulating a criminological prognosis of an offender - Kowalewska-Łukuć, Magdalena; Burdziak, Konrad (Technium Social Sciences Journal, 2021)
The article raise the issue of the use of AI (artificial intelligence) in formulating the criminological prognosis of an offender. The issue is analyzed in view of the institution of conditional early release from serving the rest of the imprisonment sentence. The authors point to several AI tools for making offender criminological predictions. An analysis of their application in various European countries shows that the question of whether their use should be considered ought to be replaced with the question of whether their use should be considered probably ought to be replaced with the question of how to use them, so that they can actually meet the objectives set for them.